Chad Systematic Country Diagnostic : Boosting Shared Prosperity in a Landlocked Country Beset by Fragility and Conflict - World Bank (Washington, DC, 2022)
Chad remains among the least developed countries in the world, and its GDP per capita has contracted since 2015. Its gross domestic product (GDP) per capita (in constant 2010 US dollars) was US$710 in 2019, down significantly from US$961 in 2014 and lower than the average of US$840 and US$1,590 in low-income countries and Sub-Saharan Africa (SSA), respectively. Mirroring this poor economic performance, the country ranked 187th out of 189 countries on the Human Development Index in 2020, and access to basic services and infrastructure is low compared to regional and structural peers. The SCD proposes six solution areas to address the binding constraints to poverty reduction. The first set includes three cross-cutting prerequisites that are critical to: strengthen the social contract, improve the management of natural resources and adapt to climate change; and achieve adequate macro-fiscal management as well as a business-friendly environment. These prerequisites are particularly important to address constraints associated with conflict, oil price volatility, climate change, and weak public administration. The second set of solutions includes three pathways aimed at raising worker productivity and improving access to improved earning opportunities: (a) supporting improvements in human capital to improve worker productivity; (b) improving Infrastructure to raise productivity, and (c) promoting sectors with a strategic advantage for more and better jobs.